TINDAK PIDANA PENGGELAPAN KARENA PENGUASAAN BARANG DISEBABKAN ADANYA HUBUNGAN KERJA: The Criminal Action Of Embracing Due To Control Of Goods Caused By An Work Relationship - Yeka Sapitri; Aprima Suar (Universitas Trisakti, 2024)
It started from the Paseban Motor Showroom, which has an inventory of motorbikes in the showroom that are used by employees who have a working relationship to commit embezzlement. The formulation of the problem in this writing is whether the crime of embezzlement due to the possession of goods is caused by a working relationship following Article 372 of the Criminal Code and how the sentence is canceled by a judge for one year and eight months in prison according to the purpose of sentencing. The research was conducted normatively with the nature of descriptive-analytical research and concluded using deductive logic methods. Of the offender's actions, it is not appropriate to be subject to Article 372 of the Criminal Code, so it is more appropriate to be subject to Article 374. The form of punishment is also inappropriate considering that there was an error in the application of the article so that the Judge cannot decide on the ultra petite and can only be guided by the existing indictment as Article 182 paragraph (3) ) and (4) Criminal Procedure Code.